There are no numerical values available so you cannot actually "solve" this equation but you can make h the subject (that is, h=) and then if you obtain values, you can go straight to solving h.
This is an equation so can be manipulated like any equation
So to make h the subject, factorize:
2A = ha + hb becomes
2A= h(a + b).
To get h by itself divide by (a+b) - the opposite operation of times.It stands as h x (a+b) so becomes:
`(2A)/(a+b) = h`
`therefore h= (2A)/(a+b)`
you can factor out the h as both a and b are multiplied by h
2A= h (a+b)
now divide by a+b to get h alone
`(2A)/(a+b)= (h (a+b))/(a+b) `